Pemanfaatan Assemblr Edu dalam Pembelajaran Simulasi Komputer: Pengaruhnya terhadap Minat Belajar Siswa - Muthia, Muthia; Pobela, Elvira Ningsih; Latief, Mukhlisulfatih; Novian, Dian; Dwinanto, Arif; Mas'ud, Huzaima (Universitas Negeri Gorontalo, 2025)
In the educational process, there are various factors that influence the success of the learning process, one of which is student interest in learning. However, in practice, there are still a number of problems related to low student interest in learning. One of the causes is the lack of interesting learning media and abstract learning materials, which cause students to lose interest and feel bored in learning. This situation has an impact on low student interest in learning. This study aims to examine the effect of Assemblr Edu-based learning media on students' interest in learning, particularly in Von Neumann computer simulation material. The media validation results showed a percentage of 88%, indicating that Assemblr Edu-based learning media is suitable for use. Additionally, the hypothesis test using the independent samples t-test method yielded a Sig value of 0.009 < 0.05, where the result is smaller than Sig 0.05, meaning there is an effect on students' interest in learning. This finding indicates that Assemblr Edu-based learning media influences students' interest in learning.